Public Event: Global to Village: Grounding Communication Research in Rural China - Ackerley, Christine Rose (Stream: Interdisciplinary Journal of Communication, 2015)
The M.A. Double Degree Program in Global Communication is holding a workshop on ethnographic research in rural China, to share their initial analysis and experiences in the field. The workshop will be at SFU Harbour Centre, room 1530 from 7 pm to 9 pm on November 12. Please see the attached poster for details.